Fungal pathogens associated with Rhizophora mucronata a comparative study between oiled and unoiled sites within Taklong Island National Marine Reserve (TINMAR), Nueva Valencia, Guimaras. - Perucho, Nueva Joy A.
Majority of researches on impacts of oil spills on mangroves focused on the immediate post-spill acute effects. However, the persistince of oil in sediments at oil spill sites has been reported in a number of published works. As such, this remaining oil could serve as a source of stress to mangroves resulting into the expression of sub-lethal effects such as changes in foliage and canopy, abnormalities in reproductive structures among others. Furthermore, oil in mangroves also has the potential of increasing fungal attacks due to their impairment of natural defense mechanisms such as removal from leaves and trunks. Thus, this study was conducted to determine if there was a difference in fungal species composition and frequency occurrence of fungal population of mangrove leaves collected in oiled and unoiled areas within Taklong Island National marine Reserve, Nueva Valencia, Guimaras following the spill that occurred in August 11, 2006. Fungi from diseased leaves of Rhizophora mucronata were isolated and characterized using Acidified Potato Agar (APDA) for samples collected in January 2009 only. A total of 16 species were identified among the isolates in oiled and unoiled sites. Although there is no difference in species composition, the species occuring very frequent (>10 percent frequency of occurence are different in the oiled sites than the unoiled sites. Only Monila sitophila (17.3 percent) was the very frequently isolated species in unoiled sites while Aspergillus ochraceous (12.1 percent), Cladosporium herbarum (10.6 percent) and Monila sitophila (10.6 percent) composed the very frequent species among samples collected from oiled sites. The results may imply that difference in frequency of occurrence of certain species might be an indicator for sublethal effects of oil but needs further investigations to consider environmental factors among other factors.